2021
DOI: 10.17504/protocols.io.bwm5pc86
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral sequence identification SOP with VirSorter2 v3

Abstract: This protocol shows how to use VirSorter2, checkV, DRAMv and some manual curation criteria for viral sequence identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The quality of viral contigs predicted from all three tools was assessed with CheckV v0.8.1 [50], and resulting trimmed viral sequences were annotated with DRAM v1.3 [51]. Annotated viral sequences were manually curated following the selection criteria outlined by Guo et al [52]. Additionally, viral sequences with the most confident prediction scores from DeepVirFinder (with corresponding viral scores ≥ 0.95, 𝑝 ≤ 0.05, and length ≥ 10 kb) and from VIBRANT (with corresponding quality scores of "high quality draft" or "complete circular", and length ≥ 10 kb) were retained.…”
Section: Recovery Of Viral Populationsmentioning
confidence: 99%
“…The quality of viral contigs predicted from all three tools was assessed with CheckV v0.8.1 [50], and resulting trimmed viral sequences were annotated with DRAM v1.3 [51]. Annotated viral sequences were manually curated following the selection criteria outlined by Guo et al [52]. Additionally, viral sequences with the most confident prediction scores from DeepVirFinder (with corresponding viral scores ≥ 0.95, 𝑝 ≤ 0.05, and length ≥ 10 kb) and from VIBRANT (with corresponding quality scores of "high quality draft" or "complete circular", and length ≥ 10 kb) were retained.…”
Section: Recovery Of Viral Populationsmentioning
confidence: 99%
“…1.2.2 (84) using default parameters. Viral contigs were subsequently conservatively manually curated using custom scripts and supervised screening based on combinations of viral and host gene counts from CheckV , hallmark gene counts from VirSorter2 , contig score, and gene-level annotations from DRAMv following previously benchmarked protocols (85) to remove potential false positive predictions (broadly screening for enrichment in viral-like or viral hallmark genes; depletion in host genes), retaining 12,843 total contigs from metagenomes, and 214 total contigs from metatranscriptomes. Manually curated dsDNA, ssDNA, and RNA viral sequences were clustered at 95% minimum sequence identity within coassembly using CD-HIT-EST ver.…”
Section: Methodsmentioning
confidence: 99%
“…Reads were reassembled using metaplasmidSPAdes (Antipov et al, 2019) to look for contigs with overlapping ends, indicative of circular genomic regions, commonly viral or plasmid in origin. To remove potential viruses, putative plasmids identified as viral by VirSorter2 v2.2.3 (Guo, Bolduc, et al, 2021) and CheckV v0.8.1 (Nayfach et al, 2021) as outlined in their best practice protocol (Guo, Vik, et al, 2021) or identified as viral from Kaiju or Kraken2 were discarded. Putative non-viral plasmids were then checked against PlasClass v1st/Nov/2021 (Pellow et al, 2020) and any contig with a score of less than 0.5 was discarded as a false positive, as outlined in Pellow et al (2020).…”
Section: Methodsmentioning
confidence: 99%